Drivers' unsafe behaviors in Iran: An investigation in West Azerbaijan - Bakhtari Aghdam, Fatemeh; Shaheian, Karim; Sadeghi-Bazargani, Homayoun; Kousha, Ahmad; Ponnet, Koen; Abbasalizad Farhangi, Mahdieh; Jahangiry, Leila (Frontiers in Public Health, 2022)
Background: The present study aims to investigate one of the major causes of traffic accidents: drivers’ unsafe behaviors while driving. Methods: In this cross-sectional study, the behaviors of 946 drivers at traffic lights were observed in the morning, at noon, and in the evening using direct in-field observation. The unsafe behaviors of the drivers included not fastening the seat belt, using a cellphone or handsfree device, smoking, being distracted by a child, talking with passengers, not observing the stop line, eating and drinking, and getting out of the car, letting out a passenger, or arguing with a passenger at the traffic light. Results: Of the drivers at the traffic light, 60% did not obey the stop line, and 72% did not fasten their seat belt. Also, 13.6% used their cellphones, and 22% talked with passengers. The frequency of the other unsafe behaviors was less than 3%. For wearing seat belts, drivers aged 41–50 years wore seat belts almost five times more than drivers under 25 years of age (4.94 [2.36–10.320]; p<0.001), and drivers aged 50 years and older were almost three times likelier to wear seat belts than drivers under 25 years of age (2.8 [1.31–6.08]; p<0.001). The results showed that the drivers were significantly likelier to wear seat belts on Saturdays (after the weekend) (0.56 [0.40–0.78]; p=0.001). Regarding using mobile phones while driving, women were twice as likely to use mobile phones as men (2.20 [1.30–3.72]; p<0.001). Drivers aged 26–40 years used mobile phones significantly less than drivers under 25 years of age (0.24 [0.14–0.43]; p<0.001) and drivers aged 41–50 years were significantly less likely to use mobile phones than drivers under 25 years of age (0.19 [1.31–6.08]; p<0.001). Conclusion: The results showed that the occurrence of wearing a seat belt in Shahin Dej was low. We observed a significant association between wearing a seat belt, age, whether it was Saturday (a day after weekend for Iranians). Additionally, similar associations were observed between using mobile phones and gender, age, and day of the week.